Effect of Aflatoxin B1 on Growth of Bovine Mammary Epithelial Cells in 3D and Monolayer Culture System - Babak Qasemi-Panahi; Taher Harkinezhad; Ali Forouharmehr (Tabriz University of Medical Sciences, 2013)
Purpose: Many studies have been showed transfer of aflatoxins, toxins produced by Aspergillus flvaus and Aspergillus parasiticus fungi, into milk. These toxins are transferred into the milk through digestive system by eating contaminated food. Due to the toxicity of these materials, it seems that it has side effects on the growth of mammary cells. Therefore, the present work aimed to investigate possible toxic effects of aflatoxin B1 (AFB1) on bovine mammary epithelial cells in monolayer and three-dimensional cultures. Methods: Specimens of the mammary tissue of bovine were sized out in size 2×2 cm in slaughterhouse. After disinfection and washing in sterile PBS, primary cell culture was performed by enzymatic digestion of tissue with collagenase. When proper numbers of cells were achieved in monolayer culture, cells were seeded in a 24-well culture plate for three-dimensional (3D) culture in Matrigel matrix. After 21 days of 3D culture and reaching the required number of cells, the concentrations of 15, 25 and 35 μL of AFB1 were added to the culture in quadruplicate and incubated for 8 hours. Cellular cytotoxicity was examined using standard colorimetric assay and finally, any change in the morphology of the cells was studied by microscopic technique. Results: Microscopic investigations showed necrosis of the AFB1-exposed cells compared to the control cells. Also, bovine mammary epithelial cells were significantly affected by AFB1 in dose and time dependent manner in cell viability assays. Conclusion: According to the results, it seems that AFB1 can induce cytotoxicity and necrosis in bovine mammary epithelial cells.